Structure and Mechanism of Pseudomonas aeruginosa PA0254/HudA, a prFMN-Dependent Pyrrole-2-carboxylic Acid Decarboxylase Linked to Virulence - Payne, Karl A. P. (ACS Catal, 2021)
[Image: see text] The UbiD family of reversible (de)carboxylases depends on the recently discovered prenylated-FMN (prFMN) cofactor for activity. The model enzyme ferulic acid decarboxylase (Fdc1) decarboxylates unsaturated aliphatic acids via a reversible 1,3-cycloaddition process. Protein engineering has extended the Fdc1 substrate range to include (hetero)aromatic acids, although catalytic rates remain poor. This raises the question how efficient decarboxylation of (hetero)aromatic acids is achieved by other UbiD family members. Here, we show that the Pseudomonas aeruginosa virulence attenuation factor PA0254/HudA is a pyrrole-2-carboxylic acid decarboxylase. The crystal structure of the enzyme in the presence of the reversible inhibitor imidazole reveals a covalent prFMN–imidazole adduct is formed. Substrate screening reveals HudA and selected active site variants can accept a modest range of heteroaromatic compounds, including thiophene-2-carboxylic acid. Together with computational studies, our data suggests prFMN covalent catalysis occurs via electrophilic aromatic substitution and links HudA activity with the inhibitory effects of pyrrole-2-carboxylic acid on P. aeruginosa quorum sensing.